A Review on the Causes, Effects and Mitigation of Climate Changes on the Environmental Aspects - Nda, Muhammad; Adnan, Mohd Shalahuddin; Ahmad, Kabiru Abdullahi; Usman, Nura; Mohammad Razi, Mohd Adib; Daud, Zawawi (International Journal of Integrated Engineering, 2018)
Abstract Climate change is often used interchangeably with the term global warming but, it is a much broader term which includes global warming and some other climate changes that are observed on our planet over the last few decades. In recent time climate change impacts are being felt, the average global temperature is on the rise every decade since the 1970s. Sea ice and glaciers are disappearing, rising sea levels, species are becoming extinct, droughts that render landscape more susceptible to wildfires, changing seasons and severe weather events are becoming more common. These are problems primarily caused by the emission of greenhouse gases into the environment that results to rise in global temperature. There seems to be a consensus among scientist, researchers and all other stakeholders that climate change is already happening and primarily caused by human activities, a few disagree with this view and attribute climate change as a natural phenomenon. The objective of this paper is to (i) introduce climate change in our world today, (ii) enumerate significant causes of climate change in our environment, as well as the effects (iii), suggest ways the impact of climate change due to GHG emissions and other contributors can be mitigated.